Mixtures of S. Rebaudiana Leaves and Stems Waste for Steviosides Synthesis Using Ethanol-Water Solvents - Said, N.; Zulkarnain, Jema'at; Nurfariha Fathmi, Zakaria; Siti Farhana, Haron; N. S., Ghazali; Fatimah A., Misebah (Malaysian Technical Universities Network (MTUN), 2014)
Mixtures of S.rebaudiana leaves and stems waste were applied for steviosides synthesis. The various ethanol-water as polarity solvents were employed in the ultrasound-assisted extraction (UAE). The HPLC (High Performance Liquid Chromatography) with Eurospher 100–5NH2 column at 1mL/m3 were used for steviosides analysis. The maximum yields were achieved by the time of 30 min., temperature of 40oC and ethanol-water ratio of 80:20 (v/v). The second order kinetics model best fits the obtained data with R2 and k of 0.992 and 0.02 min-1. Utilization of wastes as an alternative feed stock provides a cost-effective and environmental friendly way for steviosides extraction.More extensive investigation needs to be performed to compare the various advantageous processing and technical feasibilty.